1999
DOI: 10.1002/(sici)1097-4660(199906)74:6<519::aid-jctb73>3.0.co;2-q
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic model-aided reactor design for peroxidase-catalyzed removal of phenol in the presence of polyethylene glycol

Abstract: A batch-mixed reactor and a plug-¯ow reactor were shown to have identical reaction kinetics for peroxidase-catalyzed removal of phenol. Semi-batch operation and step-addition operation of the plug-¯ow reactor with respect to hydrogen peroxide produced similar output. In the presence of polyethylene glycol, a continuous stirred tank reactor needed a long time to complete the reaction at the minimum enzyme dose. It was not necessary to stir the reaction mixture continuously during the reaction, hence polymerizat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(6 citation statements)
references
References 13 publications
0
6
0
Order By: Relevance
“…There are varying results and evaluations in the literature. [ 25–45 ] In batch experiments, the initial DNOM concentration in the solution decreased with time. In contrast, the amount of DNOM in the influent of column experiments does not change over time.…”
Section: Resultsmentioning
confidence: 99%
“…There are varying results and evaluations in the literature. [ 25–45 ] In batch experiments, the initial DNOM concentration in the solution decreased with time. In contrast, the amount of DNOM in the influent of column experiments does not change over time.…”
Section: Resultsmentioning
confidence: 99%
“…Figure 4 shows the structures of the additives that were used in this experiment. PEG, which has been well studied as an additive, was also investigated 11, 12, 22, 23. Figure 5 shows the results of changes in the phenol removal efficiency with each additive.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, the improvement in the removal efficiency by surfactants is attributed to the suppression of the enzyme adsorption during the phenol‐polymerizing reaction. It has been reported that a high relative molecular mass PEG was incorporated into the phenol polymer resulting in inhibition of the interactions between the enzyme and the polymer 11, 23. The adsorption of enzyme on the polymer precipitate might be suppressed by the orientation of the hydrophobic groups in the surfactants to the polymer precipitate.…”
Section: Resultsmentioning
confidence: 99%
“…Peroxidase is a more widely studied enzyme while the potential of laccase has been investigated by a few workers [8][9][10][11]. Horseradish peroxidase has been widely used in the presence of H 2 O 2 , for the polymerisation of phenol and its derivatives [12]. However, since H 2 O 2 causes inhibition and deactivation of horseradish peroxidase, the use of laccase, in the presence of dissolved molecular oxygen for its catalytic activity, may be more advantageous than the peroxidase [8,[13][14][15].…”
Section: Introductionmentioning
confidence: 99%